International Political Sociology (Oxford University Press)
International Political Sociology (IPS), responds to the need for more productive collaboration among political sociologists, international relations specialists and sociopolitical theorists. It is especially concerned with challenges arising from contemporary transformations of social, political, and global orders given the statist forms of traditional sociologies and the marginalization of social processes in many approaches to international relations. IPS is committed to theoretical innovation, new modes of empirical research and the geographical and cultural diversification of research beyond the usual circuits of European and North-American scholarship.
Keywords: Political Sociology